2019
DOI: 10.1371/journal.pone.0221527
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected endemism in the Daphnia longispina complex (Crustacea: Cladocera) in Southern Siberia

Abstract: The biological significance of regional cladoceran morphotypes in the montane regions of the central Palearctic remains poorly understood. In the Holarctic Daphnia longispina complex (Cladocera: Daphniidae), several variants, lineages and species have been proposed as endemic for Southern Siberia. Daphnia turbinata Sars, for example, named after its unusual head shape, is known only from Southern Siberia. Here we sequence DNA of Daphnia from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 96 publications
3
19
0
Order By: Relevance
“…Phylogeographic studies confirm a special status of the Beringian zone and a specific history of the taxon dispersion there. As a result of the works on the cladoceran taxa distribution, the separation of two main biogeographic provinces (Western Holarctic Province and Beringian Province) of the Holarctic with a transitional zone in Eastern Siberia was shown [54][55][56]. Crustaceans species here can differ from that in other regions due to the differences in geological and climatic events during the last glacial maximum and previous Pleistocene glacial cycles.…”
Section: Fauna and New Records For The Regionmentioning
confidence: 79%
“…Phylogeographic studies confirm a special status of the Beringian zone and a specific history of the taxon dispersion there. As a result of the works on the cladoceran taxa distribution, the separation of two main biogeographic provinces (Western Holarctic Province and Beringian Province) of the Holarctic with a transitional zone in Eastern Siberia was shown [54][55][56]. Crustaceans species here can differ from that in other regions due to the differences in geological and climatic events during the last glacial maximum and previous Pleistocene glacial cycles.…”
Section: Fauna and New Records For The Regionmentioning
confidence: 79%
“…Previous studies have already shown a rich genetic/haplotype diversity of cladocerans in the Eastern Palearctic (e.g., Bekker et al 2018; Ma et al 2019 b ), especially in Siberia (Zuykova et al 2019). Consistent with this, we detected high haplotype diversity in C. sphaericus populations in China.…”
Section: Discussionmentioning
confidence: 96%
“…For example, the only representatives of the D. longispina species complex found in China to date are D. galeata Sars, 1863, D. longispina Muller, 1776 and D. dentifera Forbes, 1893 (e.g., Xu et al 2018; Ma et al 2019 a ). These three and additional species from this complex were detected in Siberia, to the north of China (Zuykova et al 2018; Zuykova et al 2019). A high species diversity of cladocerans is not always the rule (even in the same geographical region), because different species have different demographic histories (e.g., Zuykova et al 2018), as well as different evolutionary and biogeographical histories (Kotov et al 2016).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The observed phylogenetic structure of D. magna could be explained by strong founder effects that are persistent through time (De Meester et al, 2002), by genetic drift (De Gelas & De Meester, 2005), or local adaptation (Boersma et al, 1999). Indeed, a strong founder effect has been recently demonstrated in high-altitude D. longispina populations from the Altai and Sayan Mountains (Zuykova et al, 2019).…”
Section: Discussionmentioning
confidence: 97%